2017
DOI: 10.24190/issn2564-615x/2017/01.09
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects induced by Gadolinium nanoparticles on Lymphocyte A20 cell line

Abstract: Gadolinium nanoparticles (GdNPs) are potential agents for MRI of lymph nodes. The aim of this study was to evaluate the in vitro effects of 1 μM, 2.5 μM and 5 μM of GdDOTA⊂CS-TPP/HA and GdDOTP⊂CS-TPP/HA NPs on A20 lymphocyte cells exposed for 6 and 24 hours. The total cellular biomass (SRB), lactate dehydrogenase activity (LDH) and oxidative stress parameters, such as reactive oxygen species generation (ROS), reduced glutathione (GSH), malondialdehyde (MDA) and advanced oxidation protein products (AOPP) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…No topological differences could be noticed according to CS concentration, the acid or the gadolinium contrast agent. In any case, NGs diameters calculated from the AFM images were highly inferior to 100 nm ( Table 2 ) as already demonstrated before [ 66 ].…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…No topological differences could be noticed according to CS concentration, the acid or the gadolinium contrast agent. In any case, NGs diameters calculated from the AFM images were highly inferior to 100 nm ( Table 2 ) as already demonstrated before [ 66 ].…”
Section: Resultssupporting
confidence: 79%
“…A previous study on A20 cells viability [ 66 ] revealed that, while GdDOTA-NGs had no significant effect on cell survival profiles up to 24 h, GdDOTP-NGs generated a decrease of cell viability in a time- and dose-dependent manner. A20 cell line seemed to be more susceptible to Gd-based nanogels treatment compared with SVEC4-10 endothelial cell line used in the current work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Macropinocytosis, receptor-mediated endocytosis, and clathrin-mediated endocytosis are the main proposed mechanisms for transporting these nanoparticles to cells. [27][28][29] Here, Gd 3+ was successfully complexed by PO 3− and embedded within hybrid nanostructures to prevent cell penetration and toxicity. To sum up, the HNPs/catechol-coated ETT showed good biodegradability, controlled ion release, and low toxicity (Fig.…”
Section: Paper Biomaterials Sciencementioning
confidence: 99%